Bepridil reducing levothyroxine-induced enhancement of mitochondria Ca2+ Mg(2+)-ATPase activity in rat cerebrum - Chen Ding-Ding; Dai De-Zai; Chu Yong-Xin (Acta Pharmacologica Sinica, 2016)
AIM: To study if bepridil (Bep) could affect the enhancement of activity of cerebral mitochondria Ca2+ Mg(2+)-ATPase caused by levothyroxine (Lev) in relation to ischemic overload calcium cerebrum injury. METHODS: The experimental hyperthyroidism model with ischemic cerebrum was developed in rats by ig Lev 1 mg.kg-1.d-1 for 7 d. Ca2+ Mg(2+)-ATPase activity and its kinetic parameters were assayed. RESULTS: The activity, Vmax and Km of cerebral mitochondria Ca2+ Mg(2+)-ATPase in control rats were 3.1 +/- 0.8, 5.1 +/- 2.3 mmol.P(i).h-1/g protein and 0.81 +/- 0.08 mmol.L-1 (ATP) respectively, whereas those of hyperthyroid rats were significantly altered to 4.6 +/- 0.5, 8.5 +/- 1.9 mmol.P(i).h-1/g protein and 0.49 +/- 0.11 mmol.L-1 (ATP) respectively. After treated with Bep 10 or 20 mg.kg-1.d-1 ig for 3 d, allabove 3 parameters of the enzyme were very significantly reduced vs those of either control or hyperthyroid. CONCLUSION: Bep, via decreasing Ca2+ Mg(2+)-ATPase activity and increasing the affinity of Ca2+ Mg(2+)-ATPase to ATP, could prevent rat cerebrum from ATP depletion and ischemic overload calcium injury.